Comparison of Different Types of Cutting Devices in Surgery (Review) - Aleksandrovich Stupin, Victor; Evgenievna Manturova, Natalia; Alekseevich Donskikh, Aleksei; Vladimirovna Silina, Ekaterina (International Journal of Engineering and Technology, 2018)
The present work presents a description of various cutting devices with an emphasis on skin surgery for theÂ optimal choice of instruments in plastic surgery. Physical principles of work with aÂ description of the biological role of an ultrasonic scalpel, various laser cutting devices, electrosurgical instruments, including radiofrequency electrosurgery, are described. Studies of recent years, including systematic reviews and meta-analyzes, are devoted to comparative analysis of various cutting and coagulating devices among themselves and in comparison with the mechanical metal scalpel.Â